Proyek Demografi dalam Bayang-Bayang Disintegrasi Nasional: Studi tentang Transmigrasi di Gorontalo, 1950-1960 - Helman Manay (Jurnal Sejarah Citra Lekha, 2016)
The Republic of Indonesia faced variety problems related primarily an exploding population, national integration and distribution of welfare in the postcolonial sovereignity 1949. In the context of new state formation there were three things inter-related, because it is the most potential problems to threaten national integration. The unevennnes of well-being number of people in each island became the another factors. Java as center for beuracracy since the Dutch colonial era, it has been the most densely populated island, while outside Java island  that widely occupied by only a few people. The government decided to continue the program of colonization that would became transmigration. It was expected to press Java will be reduced significantly of demography and placing new areas of the another islands to develop their well-being condition objectively. In addition, since 1958 when facing disintegration treatment Indonesia was becoming more prominent in some areas, transmigration program geared to be knots of national integration. In the end, the plan must faced population problems and displacements in factual difficulties state financial, political conditions, and the instability of national security’s at the time. It made the governmen’s plan to move a third of the Javanese population in Java can not be executed well. By using the method of historical research, this paper about to discover the realization of the transmigration program during 1950-1960 in Gorontalo conducted in the midst of instability of national security.